Sieving Extremely Wet Earth Mass by Means of Oscillatory Transporting Platform - MihajloviÄ‡, Goran; Å½ivkoviÄ‡, Milutin (Emerging Science Journal, 2020)
The experience acquired from the exploitation has shown that problems in the work of oscillatory platforms appear after heavy rains, i.e. when the soil moisture (w) is greatly increased. Then the effect of transportation and sieving is the weakest, due to sticking moist earth for grille of the platform. Therefore, the main aim of this article was to create a complex theoretical and practical mathematical model of the processes mentioned above, in order to test how the platform works in extreme working conditions after abundant and prolonged rains. Therefore, complete research is divided into two characteristic phases: theoretical phase and experimental phase. In the theoretical research phase, dynamic modeling of the process of sieving of extremely wet earth mass was performed using the transmissional function analysis method and the method of Laplace transforms [1]. The Novelty in the theoretical model given by Equation 3 is that the existing model for sieving dry earth mass [2] has been improved by introducing delay coefficient Kt =[0...1]. In the experimental research phase, the original mathematical model was created using the multi-factor experiment plan method which will be shown, while the analysis of the experimental parameters was performed in three characteristic steps: regression analysis- dispersion analysis- decoding mathematical model [3].